ENVIRONMENTAL RECORD IN SOILS ON LOESS IN NORTHERN MORAVIA CZECH REPUBLIC - Žigová A.; Šťastný M. (My University, 2006)
The evolution of soil cover in the area of Litovel has been determined on the basis of grain-size distribution, mineralogy of clay fraction, chemical and micromorphological analyses. The object of the present study was a chronosequence of soils in Pleistocene sediments. Paleopedological data indicate that the area underwent environmental changes including several cycles of pedogenesis. This area provides evidence of at least two first-order warm periods. The highest degree of polygenesis can be demonstrated by Braunlehm-like Parabraunerde (PK V - Late Holstein Interglacial) and Chernozem which evolved from Haplic Luvisols (PK IV - warm period within the Riss glacial). The upper part of the profile documents different types of pedosediments which indicate erosion processes.
Keywords: CLAY MINERALOGY; EVOLUTION OF SOIL COVER; MICROMORPHOLOGICAL ANALYSIS; PEDOGENESIS; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен